P538 Suboptimal disease control is common in patients with Crohn's perianal fistulas with capacity to optimise medical and surgical treatment in real-world experience: A cross-sectional analysis of baseline disease characteristics in the FINESS study. (30th January 2023) - De Gregorio, M; D'Souza, B; Connell, W; Kamm, M A; Woods, R; Connor, S J; Thompson, A J; Ding, N S
Abstract: Background: Crohn's perianal fistula treatment is often challenging, requiring combined medical and surgical treatment with heterogeneity in real-world practice. We herein evaluate disease activity and management history of patients with Crohn's perianal fistulas, identifying those with active disease amenable for treatment optimisation. Methods: We present the results of a cross-sectional study of disease characteristics among patients with Crohn's perianal fistulas at a single specialist Inflammatory Bowel Disease service. Patients with Crohn's perianal fistulas seen in clinic from February 2021 to June 2022 (new and review appointments) were sequentially enrolled. Patients were excluded based on rectovaginal or rectovesical fistulas, proctectomy, pregnancy or breastfeeding. Baseline disease activity was defined as active (stage A/B: sepsis, actively draining), optimised with a chronic seton in situ (stage C), or remission (stage D: no discharge from fistula tract external opening). Radiologic disease activity was assessed with magnetic resonance imaging using the Van Assche Index (VAI), VAI-inflammatory sub-score (VAIinfl ; derived from T2-hyperintesnity, collections >3mm diameter, and rectal wall involvement), and Magnetic Resonance Novel Index for Fistula Imaging in Crohn's Disease (MAGNIFI-CD) score. Results: Sixty patients were included with a median age of 39 years (IQR 17.7), 52% male, median clinic attendance of 6 years (IQR 7.9), median Crohn's and perianal disease duration of 13 (IQR 16.8) and 8 (IQR 13.5) years, respectively. Majority were on anti-tumour necrosis factor-α therapy (28% infliximab, 40% adalimumab) and an immunomodulator (55% thiopurine, 5% methotrexate). Forty-two percent had undergone perianal surgical intervention within the preceding 12 months, see Table 1. Forty-eight percent ( n =29), 7% ( n =4), and 45% ( n =27) had stage A/B, C, and D disease activity, respectively. Radiologic disease activity scoring indices were lower between stage D and A/B (VAI 4 vs 12; VAIinfl 0 vs 8; MAGNIFI-CD 2 vs 6, respectively), see Table 2. Of those with stage A/B disease activity, 31% were not on a biologic (63% new diagnosis, 25% prior remission, 13% comorbidities precluding), 52% were infliximab naïve (71% new diagnosis, 14% prior remission, 14% contraindications), 85% who were on a biologic had potential for initial or further dose escalation, and 31% did not undergo perianal surgical intervention in the preceding 12 months. Conclusion: In a single specialist centre, almost half the patients with Crohn's perianal fistulas have clinically active disease, with capacity to optimise medical and/or surgical treatment in the majority. Prospective assessment of a model of care directed towards optimising treatment in these patients is needed.